CO2-Fixation Strategies in Energy Extremophiles: What Can We Learn From Acetogens? - Lemaire, Olivier N.; Jespersen, Marion; Wagner, Tristan (Frontiers in Microbiology, 2020)
Domestication of CO2-fixation became a worldwide priority enhanced by the will to convert this greenhouse gas into fuels and valuable chemicals. Because of its high stability, CO2-activation/fixation represents a true challenge for chemists. Autotrophic microbial communities, however, perform these reactions under standard temperature and pressure. Recent discoveries shine light on autotrophic acetogenic bacteria and hydrogenotrophic methanogens, as these anaerobes use a particularly efficient CO2-capture system to fulfill their carbon and energy needs. While other autotrophs assimilate CO2 via a carboxylation followed by a reduction, acetogens and methanogens do the opposite. They first generate formate and CO by CO2-reduction, to subsequently fix them to funnel the carbon towards their central metabolism. Yet, their CO2-reduction pathways, with acetate or methane as end-products, constrain them to thrive at the “thermodynamic limits of Life”. Despite this energy restriction, acetogens and methanogens are growing at unexpected fast rates. To overcome the thermodynamic barrier of CO2-reduction they apply different genius chemical tricks such as the use of flavin-based electron-bifurcation or coupled reactions. This mini-review summarizes the current knowledge gathered on the CO2-fixation strategies among acetogens. While extensive biochemical characterization of the acetogenic formate-generating machineries has been done, there is no structural data available. Based on their shared mechanistic similarities, we apply the structural information obtained from hydrogenotrophic methanogens to highlight common features, as well as the specific differences of their CO2-fixation systems. We will discuss the consequences of their CO2-reduction strategies on the evolution of Life, their wide distribution and their impact in biotechnological applications.